A longitudinal linguistic analysis of written text production in a case of semantic variant primary progressive aphasia. (August 2016) - Heitkamp, Nari; Schumacher, Rahel; Croot, Karen; de Langen, Ernst G.; Monsch, Andreas U.; Baumann, Thomas; Danek, Adrian
Abstract: The semantic variant of primary progressive aphasia (svPPA) presents with a degradation of semantic knowledge due to atrophy of the anterior temporal lobe and is characterized by impaired confrontation naming and impaired single-word comprehension. So far, little is known about the development of symptoms and their order of occurrence in the preclinical phase, and information regarding written text production is scarce. We had the unique opportunity to analyze the diary of a man written over a time span of 12 years before he was diagnosed with svPPA. We sought to identify the earliest indicators of cognitive change in his diary entries, and to track the important changes over time. Based on transcripts of the entries (one week every six months) we assessed the overall structure, vocabulary, surface dysgraphia and semantic paraphasia, syntax, and morphology. We found changes in all domains up to seven years before the clinical diagnosis. The earliest changes concerned the vocabulary, with decreased variety and increased use of high frequency words. This was followed by syntactic and morphological errors. We found no increase of surface dysgraphia. Semantic paraphasias increased only during the last three years but characterized the entries of the last year. We were therefore able to further corroborate recent findings regarding difficulties in the morpho-syntactic domain in this patient group. In this natural context for written text production, such errors seem, in addition to changes in vocabulary, to be the first error types to appear, possibly as a result of compensating for the degradation of semantic representations. Highlights: First linguistic study on naturalistic written text production in a case of svPPA. Based on diary entries of twelve years prior to clinical diagnosis. Changes in language use detectable seven years prior to diagnosis. First changes concern vocabulary and morpho-syntactical errors. Semantic errors occur relatively late.